The general principles and methods of treatment of pulmonary tuberculosis - Yasinskiy, R. M.; Solodovnik, Yu. S.; Ясінський, Роман Миколайович; Солодовник, Юрій Семенович (Zaporozhye state medical university, 2015)
The study guide is made according to the work program of phthisiology for students – foreign citizens of 4th course for practical classes. The manual described the history of tuberculosis treatment, the general principles and methods of treatment, medicines to treat pulmonary tuberculosis and patients’ treatment regimens.